Astragalus mongholicus Bunge (Fabaceae): Bioactive Compounds and Potential Therapeutic Mechanisms Against Alzheimer’s Disease - Dong, Qianyu; Li, Zhen; Zhang, Qian; Hu, Yueyu; Liang, Huazheng; Xiong, Lize (Frontiers in Pharmacology, 2022)
Astragalus mongholicus Bunge [Fabaceae] (also known as Astragali Radix-AR), a widely used herb by Traditional Chinese Medicine practitioners, possesses a wide range of pharmacological effects, and has been used to treat Alzheimer's disease (AD) historically. Its bioactive compounds are categorized into 4 families: saponins, flavonoids, polysaccharides, and others. AR’s bioactive compounds are effective in managing AD through a variety of mechanisms, including inhibiting Aβ production, aggregation and tau hyperphosphorylation, protecting neurons against oxidative stress, neuroinflammation and apoptosis, promoting neural stem cell proliferation and differentiation and ameliorating mitochondrial dysfunction. This review aims to shed light upon the chemical constituents of AR and the mechanisms underlying the therapeutic effect of each compound in manging AD. Also presented are clinical studies which reported successfully management of AD with AR and other herbs. These will be helpful for drug development and clinical application of AR to treat AD.